Expanded dengue syndrome presented with rhabdomyolysis, compartment syndrome, and acute kidney injury: A case report. Issue 7 (18th February 2022) - Arif, Aabiya; Abdul Razzaque, Muhammad Raheel; Kogut, Lucas Marian; Tebha, Sameer Saleem; Shahid, Filza; Essar, Mohammad Yasir
Abstract: Rationale: Expanded dengue syndrome (EDS) is the phenomenon coined by the World Health Organization for cases of dengue fever (DF) with rare but dangerous consequences. EDS mainly leads to complications involving the vital organs, thus is also associated with a higher mortality rate. This case report presents the first-ever case where a patient developed EDS with both rhabdomyolysis-induced acute kidney injury and compartment syndrome of the limbs. Patient concerns: Our patient, an 18-year-old Pakistani male, presented with fever, colicky abdominal pain, vomiting, diarrhea, dark-colored urine, and oliguria. Diagnoses: Dengue rapid NS-1 test came back positive. Along with myoglobinuria both serum creatine phosphokinase and creatine levels were abnormal. Hence, the patient was diagnosed with rhabdomyolysis-induced acute kidney injury. On physical examination, his right arm was painful and tender with restricted movement at the elbow. A Doppler ultrasound of the arm revealed thickening of the skin and underlying muscles, as well as edematous abnormalities affecting the entire right upper limb, both of which are indications of compartment syndrome. Interventions and outcome: The management included rehydration, administration of dextrose and bicarbonate (bicarbonate infusion) prepared by adding 150 mEq sodium bicarbonate in 850 mL dextrose 5%, pain killers, along with platelet, and packed red cell transfusions. Additionally, right upper limb was kept elevated at 90° for 30 minutes every 2 hours to reduce edema and crept bandages were applied. The patient was discharged after 11 days and the follow-up was uneventful. Lesson: Physicians should be aware that rhabdomyolysis-induced acute kidney damage and limb compartment syndrome are also possible DF consequences, and they should be on the lookout for any indications pointing to these complications in DF. A prompt diagnosis can prevent further complications and fatality.